Horizontal evaluation: Stimulating social learning among peers - Thiele, Graham; Devaux, A.; Velasco, C.; Manrique, K. (2006)
Horizontal evaluation is a flexible evaluation method that combines self-assessment and external review by peers. We have developed and applied this method for use within an Andean regional network that develops new methodologies for research and development (R&D). The involvement of peers neutralizes the lopsided power relations that prevail in traditional external evaluations, creating a more favourable atmosphere for learning and improvement. The central element of a horizontal evaluation is a workshop that brings together a group of ‘local participants’ who are developing a new R&D methodology and a group of ‘visitors’ or ‘peers’ who are also interested in the methodology. The workshop combines presentations about the methodology with field visits, small group work and plenary discussions. It elicits and compares the perceptions of the two groups concerning the strengths and weaknesses of the methodology; it provides practical suggestions for improvement, which may often be put to use immediately; it promotes social learning among the different groups involved; and it stimulates further experimentation with and development of the methodology in other settings.